2002
DOI: 10.1128/jb.184.22.6289-6300.2002
|View full text |Cite
|
Sign up to set email alerts
|

Gene Structure, Organization, Expression, and Potential Regulatory Mechanisms of Arginine Catabolism inEnterococcus faecalis

Abstract: Although Enteroccus faecalis is the paradigm for biochemical studies on the arginine deiminase (ADI) pathway of fermentative arginine catabolism, little genetic information exists on this pathway in this organism. We fill this important gap by characterizing, in an 8,228-bp region cloned from a gt11 genomic library of E. faecalis, a five-gene cluster forming a transcriptional unit (revealed by Northern blots and primer extension in E. faecalis) that corresponds to the ADI operon. Four additional genes in the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
101
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(106 citation statements)
references
References 71 publications
4
101
1
Order By: Relevance
“…The presence of two arginine regulator homologues in Enterococcus faecalis has recently been described (2). Only a single Asp residue, as is the case for ArgR Ll , is present in the putative arginine-binding region of both E. faecalis homologues, leading to the suggestion that these regulators may bind metabolites other than arginine.…”
Section: Vol 186 2004 Regulation Of Arginine Metabolism In L Lactimentioning
confidence: 99%
“…The presence of two arginine regulator homologues in Enterococcus faecalis has recently been described (2). Only a single Asp residue, as is the case for ArgR Ll , is present in the putative arginine-binding region of both E. faecalis homologues, leading to the suggestion that these regulators may bind metabolites other than arginine.…”
Section: Vol 186 2004 Regulation Of Arginine Metabolism In L Lactimentioning
confidence: 99%
“…In S. mutans and E. faecalis, the AgDS closely resembles the arginine deiminase system (ADS), a pathway that generates ammonia, CO 2 , and ATP from arginine (4,6,13,23,33,37,39). The ADS is considered a primary mechanism of acid tolerance used by some oral bacteria to survive the frequent cycles of acidification encountered in den-tal plaque, but it is not present in the genome of S. mutans (9).…”
mentioning
confidence: 99%
“…Despite differences in the organization of genes involved in arginine metabolism, experimental evidence indicates that the mechanism of arginine-dependent regulation of these genes is highly conserved among a range of different organisms, including Gram-negative, Gram-positive and extremophilic bacteria (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Regulation is exerted by binding of single transcriptional regulators of the ArgR family to so-called ARG operator sites preceding the relevant target genes, generally leading to repression of arginine biosynthetic genes and activation of catabolic genes, in the presence of arginine.…”
mentioning
confidence: 99%
“…A few recent investigations have proven that these ArgR homologues are not merely orthologous but fulfill distinct functions in these organisms. A study in Enterococcus faecalis revealed the presence, upstream of the arginine catabolic arcABCRD operon, of two genes named argR1 and argR2 (10). Although the function of the E. faecalis ArgR-type regulators was not investigated, it was proven that the divergently transcribed argR1 and argR2 genes were differentially expressed in response to arginine and glucose, possibly via putative ARG boxes preceding the genes (10).…”
mentioning
confidence: 99%
See 1 more Smart Citation